Analisis Rasio Likuiditas dan Profitabilitas Untuk Menilai Kinerja Keuangan Koperasi (Studi Kasus Pada KSP Kopdit Pintu Air Tahun 2019–2021) - Valeria Eldyn Gula; Katharina Yuneti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Financial ratio analysis is the basis for assessing the performance of cooperatives in managing their funding sources in a certain period. An analysis of KSP Kopdit Pintu Air's financial performance is carried out in relation to the importance of assessing the company's financial performance so that it becomes an evaluation of the company's future development. In particular, researchers assess the company's financial performance based on the ratio of liquidity and profitability.The research method used is a quantitative method with a descriptive format. The results of the calculation of the ratio are then compared with the standard Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia No.06/Per/M.KUKM/V/2006 concerning Guidelines for the Assessment of Achievement Cooperatives. The results of the study show that the financial performance of KSP Kopdit Pintu Air for 2019-2021, when viewed from the aspects of liquidity and profitability, is generally still below the standards of the Minister of Cooperatives and SMEs of the Republic of Indonesia No.06/Per/M.KUKM/V/2006. KSP Kopdit Pintu Air should make improvements to assets and KSP Kopdit Pintu Air should also reduce and reduce the amount of current debt and further increase the current assets of the cooperative.